Assessment of Knowledge and Awareness Regarding Osteopenia Among University Students: Knowledge and Awareness Regarding Osteopenia - Naveed, Ashna; Noreen, Sana; Rizwan, Bahisht; Fatima, Sana; Mudassir, Alina; Rehman, Ureeba; Sajjal, Fatima; Khalid, Ammara; Sajjad, Zainab; `Junaid, Naila (Pakistan Journal of Health Sciences, 2023)
Osteopenia is a term that identifies disproportionate bone mass loss. Osteopenia is caused by severe malnutrition and several abnormalities, which include osteomalacia, osteoporosis and cancer. Objective: To assess the knowledge toward calcium intake and the level of awareness about osteopenia among university students. Methods: For this study, the cross-sectional method was used as a study design. The study was conducted among students at the University of Lahore in which there were 100 students between 18-30 years’ old who took part in this study and time duration of study is 4 months. Moreover, probability convenient sampling technique was used, and a questionnaire was used as equipment for this study. For the statistical analysis SPSS version 24.0 for used. Results: The result of this study shows out of the sample, 25% were male, and 75% were female. The 50 belonged to the normal BMI, 2 were obese range of BMI, 31 belonged to the underweight category. 73 participants belonged to urban areas whereas 27 participants belonged to rural areas. The frequency distribution showed that 96% of people knew about calcium deficiency, and 4% were unaware. 88% of people knew about the importance of calcium, and 12% people were not aware. Conclusions: Chronic calcium deficiency contributes to osteoporosis, poor mineralization of bones and soft bone osteomalacia. According to results, people now a days are more eager to change their dietary patterns to help improve their bone health.